EFFECTIVENESS OF NIFEDIPINE IN EXTERNAL CEPHALIC VERSION - Rauf, Bushra; Ali, Sadia (Journal of Postgraduate Medical Institute, 2017)
Objective: To find out the effectiveness of oral nifedipine as a tocolytic agent in external cephalic version. Methodology: This was an observational study carried out in the private clinical setting of Peshawar Health Center from Nov 15, 2014 till Nov 15, 2015. It included patients presenting with uncomplicated singleton breech fetuses between 36 to 41 weeks of period of gestation. All the patients were given a 10mg oral tablet of nifedipine, 15 minutes prior to the procedure. A pre-procedure ultrasound was done for assessment of fetal parameters, following which gentle attempt of external cephalic version (ECV) was made. Success of the procedure in terms of persistent cephalic presentation was recorded as the primary outcome. Any feto-maternal complications were noted as the secondary outcomes. A post procedure ultrasound was carried out for fetal reassurance and confirmation of fetal position. Results: A total of 58 patients were recruited in this study. Success rate of oral nifedipine was 77.6%. It was significantly higher (71.1%) in multigravida (p value 0.03) and in patients with flexed breech (84.6%) (p value 0.0001). No significant association was found with gestational age of the fetus and successful outcome. Conclusion: Nifedipine is a good choice as tocolytic agent in ECV, with no maternal or fetal complications and with better outcome in terms of success of ECV.